(untitled) (The Agriculturists, 2018)
The present study was conducted to assess the water quality at Chandpai range in Bagerhat district of the Sundarbans Mangrove Forest of Bangladesh. Seven water samples were collected during July to December 2014. The water were analyzed for pH, EC, P, K, S, Ca, Mg, Cu, Mn, Zn, Fe and B. The EC values of rivers and canals water were found higher than that of the ponds. River waters of Chandpai range were detected as neutral to slightly alkaline. Waters from Karamjalkhal (Lake), Pasur river, Nandabala canal and Ismails Chila were found strongly saline (EC, 8-12 dSm-1), Bholakhal (lake) was moderately saline (EC, 4-8 dSm-1) and Boiddomari and Dashervarani ponds were poorly saline (EC<4 dSm-1) in nature. The concentrations of K, Ca, Mg, S, Zn and B were found higher and P, Cu and Mn were lower at higher EC levels. The concentrations of K, S, Cu and B in most of the rivers exceeded the permissible level for aquaculture. The Agriculturists 2018; 16(2) 123-130